2014
DOI: 10.1038/nm.3552
|View full text |Cite|
|
Sign up to set email alerts
|

PAI-1 mediates the antiangiogenic and profibrinolytic effects of 16K prolactin

Abstract: The N-terminal fragment of prolactin (16K PRL) inhibits tumor growth by impairing angiogenesis, but the underlying mechanisms are unknown. Here, we found that 16K PRL binds the fibrinolytic inhibitor plasminogen activator inhibitor-1 (PAI-1), which is known to contextually promote tumor angiogenesis and growth. Loss of PAI-1 abrogated the antitumoral and antiangiogenic effects of 16K PRL. PAI-1 bound the ternary complex PAI-1-urokinase-type plasminogen activator (uPA)-uPA receptor (uPAR), thereby exerting anti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
72
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 92 publications
(75 citation statements)
references
References 49 publications
3
72
0
Order By: Relevance
“…Thus, PAI-1 and iNOS are downstream of 16-kDa prolactin but not of full-length prolactin (12)(13)(14). The 16-kDa form, but not the full-length form, requires the formation of a complex with PAI-1 to be active (41), and their intracellular signaling pathways differ (42).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, PAI-1 and iNOS are downstream of 16-kDa prolactin but not of full-length prolactin (12)(13)(14). The 16-kDa form, but not the full-length form, requires the formation of a complex with PAI-1 to be active (41), and their intracellular signaling pathways differ (42).…”
Section: Discussionmentioning
confidence: 99%
“…44,104 They showed that 16-kDa prolactin induces endothelial cells to package miR-146a into exosomes, small lipid-encapsulated particles, which are then secreted and taken up by cardiomyocytes. The miR-146a internalized into cardiomyocytes then suppresses the neuregulin/ErbB pathway, thereby promoting cardiomyocyte apoptosis.…”
Section: The Vasculo-hormonal Hypothesismentioning
confidence: 99%
“…Consistent with their ability to block the neuronal activation of the MAPK/ERK1/2 and PI3K/AKT pathways by VEGF and NGF, vasoinhibins are known to inhibit the action of several vasoactive substances including VEGF and basic fibroblast growth factor [48][49][50], and to activate protein phosphatase 2A in endothelial cells [49]. Vasoinhibins bind to a multicomponent complex formed by plasminogen activator inhibitor-1, urokinase plasminogen activator, and the urokinase plasminogen activator receptor on endothelial cells, which leads to the perturbation of signaling pathways triggered by angiogenic factors like VEGF, including MAPK/ERK [51]. Vasoinhibins also inhibit VEGF-and basic fibroblast growth factor-induced activation of the Ras-Raf-MAPK pathway [52,53], the Ras-Tiam1-Rac1-Pak1 pathway [54], and the Ca 2+ / calmodulin-mediated activation of endothelial nitric oxide synthase [50].…”
Section: Discussionmentioning
confidence: 99%